(untitled) (International journal of artificial intelligence, 2024)
In this article, the effectiveness of the strategy in school management the role in improvement has been reflected on the impact of management efficiency on the quality of Education. It is also clear by the leader in the development of the management strategy of the school it is worth noting that it is important to be able to set goals, make informed decisions considerations expressed.